Establishment of the device for separation of fibers suitable for spinning from the waste of the cotton cleaning process - Xuramova , Xadicha (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article explored a device for the separation of cotton pieces from cotton waste that were separated from the cotton waste that was separated from the processes of cleaning cotton in its original processes. The factors affecting the processing of the separation device have been taught and suggestions are made. In the separation device, differential equations of mass movement are formed and appropriate graphics are obtained.